The Curvilinear Relationships Between Top Decision Maker Goal Orientations and Firm Ambidexterity: Moderating Effect of Role Experience - Pryor, Christopher; Santos, Susana C.; Xie, Jiangpei (Frontiers in Psychology, 2021)
Ambidextrous firms are those that can simultaneously manage exploitative and explorative innovation, which is why ambidexterity is key for firms that desire to pursue strategic entrepreneurship. Researchers have explored many of the reasons why some firms are more ambidextrous than others. However, little attention has been devoted to understanding how attributes of top decision makers can influence their firms’ ambidexterity. By drawing on upper echelons theory and goal orientations research, we explain how firms’ ambidexterity can be affected by top decision makers’ motivations in achievement situations (i.e., goal orientations). Testing our hypotheses on a sample of 274 top decision makers of firms in the United States, we find that top decision makers’ learning goal orientation – their desire to take risks and maximize learning – has an inverted U-shaped relationship with ambidexterity while top decision makers’ performance prove goal orientation – their desire to demonstrate competence with existing skills – has a U-shaped relationship with ambidexterity. These effects are weaker for top decision makers who have greater role experience.